Retain or remove? Decision-making of rural industrial park redevelopment in Nanhai District, China - Liu, Zhuojun; Fang, Hongjia; Xu, Shanshan; Wu, Yilin; Wen, Keyin; Shen, Zitong; Wang, Hongmei (Frontiers in Environmental Science, 2024)
Introduction: In both of China and other industrializing countries, improving the efficiency of degraded industrial land use will help control urban sprawl brought about by rapid urbanization. The redevelopment of industrial parks in the countryside is becoming a starting point for phasing out high-polluting industries and an important source of land supply for high-end and green industries. The objective of this paper is to identify how the local state of China determines the necessity for the demolition of rural industrial parks (RIPs) and how this process reflects the underlying decision-making mechanisms. Methodology: This paper carries out descriptive spatial analysis by combining the economic and social development cross-sectional data in 2019 and extracts data from the Baidu Map to calculate the traffic network density. Cluster analysis is also used to group the RIPs according to their data characteristics. In order to provide an in-depth discussion of the cases, the authors also overlay the results of the spatial and cluster analyses. Results: The spatial distribution of RIPs is closely related to their location and transportation conditions. Failure of the market has resulted in large tracts of advantageous land being taken up by inefficient industrial parks. Cluster analysis and overlay analysis have evaluated the difficulty of redevelopment and divided the industrial parks into three clusters: retained RIPs, medium-term removed RIPs, and near-term-removed RIPs. The authors put forward that different strategies should be adopted for the future renovation of medium-term-removed and near-term-removed RIPs. Discussion: This paper argues that proper categorization is the beginning of feasible RIP redevelopment. Local governments should resist the temptation of short-term land transfer revenues to achieve long-term growth. The significant differences in concerns between the grassroots and the higher levels of government also require that the effects of bottom-up influence and top-down intervention should be balanced.